Application of WA‘D (promise) in Islamic banking products: A study in Malaysia and Bangladesh / Md. Faruk Abdullah - Md. Faruk, Abdullah (2016)

(untitled)
This research considers the practice of wa‘d in Islamic banking products in Malaysia and Bangladesh and compares between them. It discusses the Shari‘ah issues and other challenges in the practice of wa‘d. Finally, it determines the prospects of wa‘d-based products in both countries. It adopts a qualitative case study approach while choosing three Islamic banks in each country for case study. Along with library research and document analysis, it conducts interviews with Islamic banking practitioners and Shari‘ah scholars. It follows thematic and a comparative method to analyse the data. The findings of this study show that Malaysia has innovated numerous products based on wa‘d while Bangladesh has a limited number of products. The major challenge of wa‘d in Malaysia is Shari‘ah issues. However, this study concludes that Malaysian practice of wa‘d is free from the issues of Shari‘ah claimed by a few studies. Nevertheless, Malaysia should have a legal provision for wa‘d in the Contract Act and a guideline for the practice of wa‘d. In the case of Bangladesh, the major challenges of wa‘d are (1) the strictness of the Shari‘ah scholars, (2) lack of product development initiative, (3) and the absence of a legal provision for wa‘d. However, both countries have significant potential to develop a number of Islamic retail-banking and treasury products through using wa‘d.